Pengaruh Pengembangan Karir Terhadap Kepuasan Kerja di Aston Batam Hotel and Residence - Nurul Mawaddah Warahamh; Hendri Azwar (Jurnal Riset dan Inovasi Manajemen, 2025)
This study discusses how Career Development influences Job Satisfaction at Aston Batam Hotel and Residence, where this study is motivated by employee complaints obtained from observation results questionnaires and data obtained from the research location. The purpose of this study is determine how much influence Career Development has on Job Satisfaction at Aston Batam Hotel and Reseidence. The type research used is quantitative descriptive with a sampling technique using total sampling applied to 102 respondents at Aston Batam Hotel and Residence. The data Collection technique used questionnaire with skala likert which has been tested for validity and reliability. Data analysis technique consist of data description, analysis requirements test with normality test, homogeneity test, and linearity test, and hypothesis test with simple linear regression test using SPSS version 26.00. The results of this study are Career Development is included in the good category with a respondent achievement level of 80.67%, and Job Satisfaction with a respondent achievement level of 82.19%, included in the good category. The results of the determination coefficient or R Square of 0.395 were obtained, which means that there is an influence of career development on job satisfaction of 39.5% and 60.5% is influenced by other factors not explained in this study.